The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1038/s41467-020-17131-6
|View full text |Cite
|
Sign up to set email alerts
|

High-altitude populations need special considerations for COVID-19

Abstract: The atmospheric pressure that decreases with altitude affects lung physiology. However, these changes in physiology are not usually considered in ventilator design and testing. We argue that high altitude human populations require special attention to access the international supply of ventilators. Humans are naturally adapted to live at low altitude. Yet,~2% of the world's population permanently live at altitudes above 2500 meters 1. The majority of these populations live in areas that are either poor, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…This makes our results not generalizable to the rest of the country, because besides the higher population, the northern part of Yemen has different characteristics including lower temperature and higher altitude. Some studies suggest that different climatic conditions, including temperature and altitude may affect the transmission and mortality due to SARS-CoV-2 infections [ 37 , 38 ]. The case fatality rate is unclear, as most of the cases reported through the surveillance system were severe.…”
Section: Discussionmentioning
confidence: 99%
“…This makes our results not generalizable to the rest of the country, because besides the higher population, the northern part of Yemen has different characteristics including lower temperature and higher altitude. Some studies suggest that different climatic conditions, including temperature and altitude may affect the transmission and mortality due to SARS-CoV-2 infections [ 37 , 38 ]. The case fatality rate is unclear, as most of the cases reported through the surveillance system were severe.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have suggested that altitude may be a protective factor from COVID-19 (ref. 27,30-32,36-40), our analysis is the first to employ a large longitudinal database encompassing all COVID-19 cases and deaths registered in Peru through July 17, 2020 (https://www.datosabiertos.gob.pe/group/datos-abiertos-de-covid-19). In order to correct for population density, which tends to be significantly higher on the coastal lowlands, we have normalized case and death counts by population density and per million people in all districts.…”
Section: Discussionmentioning
confidence: 99%
“…These inventory shortages have placed major strains on international diplomacy, as countries have exercised restrictions of the transport of ventilators across borders, and in some cases gone as far as resorting to the confiscation of other countries' ventilators during international transit (Kamdar, 2020 ). The developing world remains most vulnerable to these shortages (Breevoort et al, 2020 ), inspiring innovative design solutions for low cost and readily transportable ventilators from youth teams. These include ventures by US university students (Levy, 2020b ; Rusch, 2020 ), as well as a team of young engineers from India, a country with an especially sparse ventilator inventory compared to the domestic population (Biswas, 2020 ).…”
Section: Youth Network and The Covid-19 Pandemicmentioning
confidence: 99%
“…Of particular interest, is the focus youth networks have made on advocating for the attention to how regional aspects of the developing world pose specific challenges to coping with a spreading pandemic. For instance, populations living in high altitude regions such as Ethiopia, Ecuador, Bolivia, and Tibet, are sensitive to environmental conditions and physiological adaptations that influence the effectiveness of common ventilator design (Breevoort et al, 2020 ). Given the limited influence these regions have in the development of traditional health care equipment, special considerations will be necessary to design and supply ventilators capable of functioning effectively for high altitude populations.…”
Section: Youth Network and The Covid-19 Pandemicmentioning
confidence: 99%